Potensi Beberapa Kultivar Puring (Codiaeum variegatum) sebagai Fitoremediasi pada Tanah Tercemar Logam Berat Tembaga (Cu) - Nurul Hikma Fajar; Cindy Agustina; Dian Ramadhani; Audya Syahra; Reski Hamdiah; Putri Dewi Suci Ramadhani; Rismawati Rismawati; Vitrani Vitrani; Bima Sardina; Andi Muh. Fathul; Andi Badli Rompegading; Uswah Trywulan Syah; Rizal Irfandi (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aimed to obtain a Puring cultivar (Codiaeum variegatum) that can adapt to heavy and robust copper (Cu) stress and test its potential as a phytoremediation plant. The method used was a randomized block design (RAK). The results showed that the number of leaves and plant height did not show a significant difference. The most important copper (Cu) convergence in the formation was found in the Teri cultivar, with a convergence level of 126,399 ppm. In conclusion, puring cultivar can be used as a phytoremediation agent in an environment contaminated with substantial copper (Cu) metal because of its long roots and does not require more expensive costs. Keywords: Puring Cultivars (Codiaeum variegatum), Copper Metal Cu, Phytoremediation